Anatomical characteristics of two enigmatic and two poorly known Pisidium species (Bivalvia: Sphaeriidae) from Southern South America - Ituarte, Cristián; Korniushin, Alexei V. (Zootaxa, 2006)
The shell morphology and anatomy of two enigmatic Pisidium species, Pisidium dorbignyi Clessin, 1879, never re-examined after the original description, and Pisidium lebruni Mabille, 1884, a species not reported again until 1995, are described. The type of P. dorbignyi (new name for Cyclas pulchella d´Orbigny, 1835) is lost, for which, and in order to define the taxonomic status of the species, a neotype is herein selected. Both species share as common features: the presence of only the anal siphonal aperture, only one pair of demibranchs, the inner and the type of nephridium, closed with lateral loop visible from dorsal view, consistently differing in shell morphology. Previously unknown details on the anatomy of Pisidium sterkianum Pilsbry, 1897 and Pisidium vile Pilsbry, 1897, particularly those concerning the type of nephridium and inner radial mantle musculature, are described and illustrated for the first time.